NILAI-NILAI PENDIDIKAN AQIDAH DALAM KITAB SYARAH USHUL IMAN DAN IMPLEMENTASINYA DALAM KEHIDUPAN SEHARI-HARI - Hardadi, (UNISAN JURNAL, 2023)
The purpose of this research is to describe Aqidah Education in the Syarah Ushul Iman book, the values ​​of Aqidah education and its Implementation in Everyday Life. The type of research in this thesis is library research. Aqidah Education in the Book of Syarah Usul Iman is to teach every Muslim about the obligation to believe in the existence of Allah, Rububiyah Allah, Uluhiyah Allah, as well as the names and attributes of Allah. it is obligatory to believe in the existence of angels, the names of angels, the characteristics of angels and the duties of angels. It is obligatory to believe that the books were sent down by Allah, the names of Allah's books, believe in the truth of Allah's books, and practice what is contained in Allah's books. it is obligatory to believe that the message of the Messenger is really from Allah, the existence of the names of Prophets and Apostles, the truth of the news conveyed by Prophets and Apostles and practice the teachings they bring. It is obligatory to believe in the events of the Last Day, such as the Day of Resurrection, the Day of Judgment, Heaven and Hell. It is obligatory to believe in the knowledge of destiny, whether it is related to knowledge, writing, will or creation. In general, there are 2 values ​​of Aqidah Education in the Book of Syarah Ushul Iman, namely Divine values ​​and Insaniyah values. And each of the 6 pillars of faith in the book Syarah Usul Iman has this value and its explanation. The Book of Syarah Ushul Iman contains the main points of the Ahlus Sunnah Wal Jama'ah faith. So that it must be known and practiced by every Muslim. As well as living the values ​​of aqidah education in everyday life.